2017
DOI: 10.1186/s12906-017-1954-2
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of calyx of Diospyros kaki Thunb. through downregulation of cyclin D1 via inducing proteasomal degradation and transcriptional inhibition in human colorectal cancer cells

Abstract: BackgroundAlthough it has been reported to contain high polyphenols, the pharmacological studies of the calyx of Diospyros kaki Thunb (DKC) have not been elucidated in detail. In this study, we elucidated anti-cancer activity and potential molecular mechanism of DKC against human colorectal cancer cells.MethodsAnti-cell proliferative effect of 70% ethanol extracts from the calyx of Diospyros kaki (DKC-E70) was evaluated by MTT assay. The effect of DKC-E70 on the expression of cyclin D1 in the protein and mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…EEDK has previously been reported to inhibit Wnt/β-catenin signaling activity. Moreover, EEDK inhibition has been shown to downregulate cyclin D1 mRNA expression 19 . However, the mechanism underlying the downregulation of Wnt/β-catenin signaling by EEDK is not fully understood.…”
Section: Resultsmentioning
confidence: 99%
“…EEDK has previously been reported to inhibit Wnt/β-catenin signaling activity. Moreover, EEDK inhibition has been shown to downregulate cyclin D1 mRNA expression 19 . However, the mechanism underlying the downregulation of Wnt/β-catenin signaling by EEDK is not fully understood.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the CCND1 gene is a proto-oncogene, which is upregulated through gene enhancement or translocation in various tumor cells. 7274 Interestingly, cyclin D1 and Ki-67 activation were previously demonstrated to be regulated via NF-κB in cancer cells and their metastatic counterparts. 7577 Moreover, we found that HCT116 cells express MMP-9 and CXCR4 and TNF-β induced the expression of these proteins, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…it has been reported that mir-365 inhibited cell cycle progression and promoted apoptosis of colon cancer cells by targeting cyclin d1 and Bcl-2 (29). diospyros kaki Thunb (persimmon) may downregulate cyclin d1 as one of the potential anticancer targets via inducing proteasomal degradation and transcriptional inhibition in human colorectal cancer cells (30). a study reported that mir-519d reduces the 5-fluorouracil resistance in colorectal cancer cells by downregulating the expression of ccnd1 (31).…”
Section: Introductionmentioning
confidence: 99%